Urine Specific Gravity in Canine: Whole or Supernatant Sample? (Global Journal of Medical Research, 2019)
The ability to concentrate and dilute urine is one of the first functions that are lost as a result of tubular damage. Specific gravity by refractometry is a method used to evaluate this function. Some authors mention that the reactive sediment, as well as the presence of large amounts of high molecular weight substances can give an overestimation of the value of the specific gravity and recommends centrifuging the sample to obtain a reliable value. In the study, 123 urine samples and their specific gravity were evaluated before and after centrifugation. This in order to evaluate if the presence of reactive sediment, glucose and protein affected the value of the density and to obtain a reliable estimate in clinical practice. No significant difference was found between pre and post-centrifugation specific gravity measurement with portable refractometer (W = 8058.5, p-value = 0.3759).
Keywords: specific gravity; refractometer; dogs